Análisis de la producción de parfait de chirimoya (Annona cherimola) como complemento al ingreso económico de las familias en la parroquia Caracol - Heleno Bone, Alexaida Isabel (2023)
The Caracol Rural Parish is one of the oldest parishes in Ecuador, it has approximately 481 years of history, the implementation of new alternatives to generate a supplement to the economic income of families through the preparation of cherimoya parfait (Annona cherimola) is a way to start a small business giving added value to said fruit that is constantly wasted due to the little importance given to it, you can obtain products derived from cherimoya that serve as raw material for marketing and in this way help development socioeconomic status of the parish. To determine the budget and profits, a table of values was created where the price of each product is collected to determine how much of the budget will be invested and how much profit will be obtained in the production of parfait, the objective of the work was to inform the population of the Caracol parish that by using cherimoya at home it is possible to generate economic income using its derivatives, in addition to cultivation, by-products can also be obtained from which various products can be obtained from its seeds and leaves. Custard apple seeds contain oils that are used in the production of cosmetics and soaps. Custard apple leaves have medicinal properties and are used to treat various diseases such as diabetes, hypertension and headaches. It is important to emphasize that most families go through a period where they do not have a very stable economic support, so they have to look for ways to support themselves and bring a bite of food home, which is where this innovative production of cherimoya parfait It will help these families by improving the economy and can even be distributed in large supermarkets. Government agencies must train small producers who understand economic and industrialization issues to increase the added value of their crops, help visualize their production and determine if it is a profitable and innovative business for national and international markets through the application of technologies. relevant.